Ethnobotanical survey and biological activity of medicinal plants used against candida albicans in Aganang local municipality - Tlaamela, Dikonketso Margaret (My University, 2019)
The use of medicinal plants is the most preferred traditional medicine in many populations, and their usage is part of an ancient oral-traditional system of knowledge that remains incompletely documented. Medicinal plants can be used following consultations with traditional healers or through self-medication. The current study focused on medicinal plants with potential to treat oral diseases, particularly oral thrush or oral candidiasis. An ethnobotanical survey was conducted to identify medicinal plants used for the treatment of oral thrush/oral candidiasis by the local people and traditional healers in Aganang Local Municipality, Limpopo Province. Permission to conduct an ethnobotanical survey was obtained from Bakone Ba Matlala A Thaba Traditional Council. The snowball method was used to select and identify traditional healers and local people. Semi-structured questionnaires and guided field walks with the traditional healers were used to obtain data. A questionnaire was designed to gather information on the names of plants used for the treatment of oral candidiasis, the source of the plants, the plant parts used, methods of preparation of medications and other information. The survey revealed that twelve plant species belonging to ten plant families were used by the local people and traditional healers for the treatment of oral candidiasis. The dominating families were Ximeniaceae and Asteraceae. The most frequently used plant species was Ximenia caffra Sond. var. caffra (65%), followed by Ximenia caffra Sond. var. natalensis (35%). Noticeably, the roots (43%) and leaves (21.4%) were mostly used by traditional healers to prepare their remedies. The mode of administration for their remedies was mainly orally and decoctions were the most preferred method of preparation. The observed transfer of indigenous knowledge to younger generations was an important practice for preserving our useful medicinal plants. Nine plant species (Artemisia afra Jacq. ex Willd., Blepharis subvolubilis subsp. subvolubilis C.V. Clarke., Enicostemma axillare (Lam.), Helichrysum caespititium (DC.) Harv., Solanum incanum L., Waltheria indica L., Ximenia caffra Sond. var. caffra, Ximenia caffra Sond. var. natalensis and Ziziphus mucronata Willd.) were selected based on the information provided by the local people and traditional healers for further phytochemicalinvestigation and biological assays. The antifungal activity of the crude extracts against Candida albicans was determined using microdilution method and bioautography assay. The leaves of Artemisia afra and Solanum incanum showed excellent antifungal activity against C. albicans with minimum inhibitory concentration (MIC) values of 0.02 mg/ml. Plant extracts of Blepharis subvolubilis subsp. subvolubilis and Helichrysum caespititium had moderate to low antifungal activity with MIC values ranging from 0.625 mg/ml to 2.5 mg/ml. Moreover, the good antifungal activity of water extracts against C. albicans confirms the efficacy of traditional methods for the treatment of oral candidiasis. In bioautography assay, more compounds were visible in dichloromethane, acetone, hexane, ethanol and ethyl acetate extracts of Ziziphus mucronata, Waltheria indica roots and Ximenia caffra var. natalensis. Benzene: ethanol: ammonia (BEA) was the best eluent solvent system, separating more active compounds, particularly in dichloromethane extracts. Based on good antifungal activity, W. indica and X. caffra var. natalensis were the most promising plant species and were selected for further isolation of active compounds. Solvent-solvent fractionation of acetone extracts of Waltheria indica roots and Ximenia caffra var. natalensis leaves was performed to successively partition the crude extracts with hexane, chloroform, ethyl acetate, butanol and water. This was followed by column chromatography on the most active fractions. Bioassay-guided fractionation of acetone extracts led to isolation of four compounds. Nuclear Magnetic Resonance and Mass Spectrometry were used to identify and characterise the isolated compounds. Compound 1 was identified as epigallocatechin gallate while compound 3 was identified as kaempferol-3-O-rhamnoside. Compounds 2 and 4 were not identified due to the presence of mixtures of long chain fatty acids.
Thesis(M.Sc.(Botany)) -- University of Limpopo, 2019
Keywords: Traditional medicine; Medicinal plants; Traditional healer; Medication; Medicinal plants; Ethonobonany; Candida albicans